2006
DOI: 10.1017/s0031182006000527
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel 3′-5′ DNA helicase fromPlasmodium falciparumand its sensitivity to anthracycline antibiotics

Abstract: Plasmodium falciparum has developed resistance to most anti-malarials; therefore, an investigation of potential targets should be performed. DNA helicases are enzymes that catalyse the unwinding of double-stranded DNA to provide single-stranded templates for DNA replication, repair and recombination. In this study, a DNA helicase (PfDH A) was purified from a crude extract of Plasmodium falciparum. DNA helicase activity was measured by assaying unwinding activity. The apparent molecular weight of PfDH A as dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…All the effective inhibitors bind strongly to DNA [39], and so they most likely interfere with PfRuvB3 unwinding function, whose domain ought to be distant from that of ATPase. PfRuvB3 is more sensitive to daunorubicin (IC 50 of 0.76 μM) than other helicases, such as P. falciparum DNA helicase A (PfDH A) [22], P. falciparum UvrD helicase (PfUDN) [40], P. falciparum 45 kDa helicase (PfH45) [41], P. falciparum 60 kDa DNA helicase (PfDH60) [42] and human DNA helicase (HDH II) [43] (IC 50s of 2.0, 4.4, 5.0 3.0, 6.23 μM, respectively). However, it is less sensitive to netropsin (IC 50 of 7.09 μM) than PfUDN, PfH45, PfDH60 and P. falciparum Dbp5/DDX19 homolog (PfD66) [44] (IC 50s of 3.3, 0.8, 0.5, 3.2 μM, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the effective inhibitors bind strongly to DNA [39], and so they most likely interfere with PfRuvB3 unwinding function, whose domain ought to be distant from that of ATPase. PfRuvB3 is more sensitive to daunorubicin (IC 50 of 0.76 μM) than other helicases, such as P. falciparum DNA helicase A (PfDH A) [22], P. falciparum UvrD helicase (PfUDN) [40], P. falciparum 45 kDa helicase (PfH45) [41], P. falciparum 60 kDa DNA helicase (PfDH60) [42] and human DNA helicase (HDH II) [43] (IC 50s of 2.0, 4.4, 5.0 3.0, 6.23 μM, respectively). However, it is less sensitive to netropsin (IC 50 of 7.09 μM) than PfUDN, PfH45, PfDH60 and P. falciparum Dbp5/DDX19 homolog (PfD66) [44] (IC 50s of 3.3, 0.8, 0.5, 3.2 μM, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is less sensitive to netropsin (IC 50 of 7.09 μM) than PfUDN, PfH45, PfDH60 and P. falciparum Dbp5/DDX19 homolog (PfD66) [44] (IC 50s of 3.3, 0.8, 0.5, 3.2 μM, respectively). Inhibition of PfRuvB3 activity by daunorubicin (IC 50 of 0.76 μM) and doxorubicin (IC 50 of 2.6 μM) did not correlate with parasite growth inhibition (IC 50s of 2.5 and 1.5 μM respectively) [22] suggesting that they may have different cell permeability and metabolic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge only a few helicases have been characterized from P. falciparum . These include two members of the DEAD‐box family namely PfDH60 and P. falciparum DNA helicase 45 (PfDH45) [20,21] (A. Pradhan and R. Tuteja, unpublished) and PfDHA, a 90 kDa DNA helicase which has been purified from P. falciparum [18]. Our studies indicated that PfDH60 contains helicase and ssDNA‐dependent ATPase activities and is expressed in schizont stages of the development of parasite [20,21].…”
Section: Helicase Signature Motifs and Plasmodium Falciparum Helicasesmentioning
confidence: 99%
“…PfDH45 is a homolog of eukaryotic initiation factor 4A contains helicase and ssDNA‐dependent ATPase activities and is expressed in all the developmental stages of the parasite (A. Pradhan and R. Tuteja, unpublished). PfDHA moves in the 3′ to 5′ direction and prefers a fork‐like substrate for its unwinding activity [18].…”
Section: Helicase Signature Motifs and Plasmodium Falciparum Helicasesmentioning
confidence: 99%